Risk and population attributable fraction of metabolic syndrome and impaired fasting glucose for the incidence of type 2 diabetes mellitus among middle‐aged Japanese individuals: Aichi Worker's Cohort Study. Issue 5 (3rd March 2020) - Kaneko, Kayo; Yatsuya, Hiroshi; Li, Yuanying; Uemura, Mayu; Chiang, Chifa; Hirakawa, Yoshihisa; Ota, Atsuhiko; Tamakoshi, Koji; Aoyama, Atsuko
Abstract: Aims/Introduction: The Japanese government started a nationwide screening program for metabolic syndrome (MetS) to prevent cardiovascular diseases and diabetes in 2008. Although impaired fasting glucose (IFG) is a strong predictor for type 2 diabetes mellitus, the program does not follow up IFG in non‐MetS individuals. This study aimed to examine the risk and the population attributable fraction (PAF) of MetS and IFG for incidence of type 2 diabetes mellitus. Materials and Methods: Japanese workers (3, 417 men and 714 women) aged 40–64 years without a history of diabetes were prospectively followed. MetS was defined as either abdominal obesity plus two or more metabolic risk factors, or being overweight in the case of normal waist circumference plus three or more metabolic risk factors. IFG was defined as fasting blood glucose 100–125 mg/dL. Results: During a mean 6.3 years, 240 type 2 diabetes mellitus cases were identified. Compared with those without MetS and IFG, the multivariable‐adjusted hazard ratios (95% confidence interval) of non‐MetS individuals with IFG, MetS individuals without IFG and MetS individuals with IFG for type 2 diabetes mellitus were 4.9 (3.4–7.1), 2.4 (1.6–3.5) and 8.3 (5.9–11.5), respectively. The corresponding PAFs for type 2 diabetes mellitus incidence were 15.6, 9.1 and 29.7%, respectively. Conclusions: IFG represented a higher risk and PAF than MetS for type 2 diabetes mellitus incidence in middle‐aged Japanese individuals. The coexistence of MetS and IFG showed the highest risk and PAF for type 2 diabetes mellitus incidence. The current Japanese MetS screening program should be reconsidered to follow up non‐MetS individuals with IFG. Abstract : The present study showed that non‐metabolic syndrome individuals with impaired fasting glucose represented a higher risk and population attributable fraction than metabolic syndrome individuals without impaired fasting glucose for type 2 diabetes mellitus incidence in middle‐aged Japanese individuals.